ANALISIS KINERJA KODE BOSE CHAUDHURI HOCQUENGHEM PADA DIRECT SEQUENCE SPREAD SPECTRUM PADA KANAL FREKUENSI SELECTIVE FADING - Wahyu Sahputra; Nyoman Pramaita; Nyoman Gunantara (Jurnal SPEKTRUM, 2025)
This study aims to analyze the performance of Bose Chaudhuri–Hocquenghem (BCH) coding (7,4) in a Direct Sequence Spread Spectrum (DSSS) system using Pseudo Noise (PN) spreading code, under frequency selective fading and white Gaussian noise (AWGN) channel conditions. Simulations were performed using MATLAB Simulink to compare the system performance against Bit Error Rate (BER) at various values of bit energy to noise power density (Eb/No). The simulation results show that the use of BCH generally improves system performance by significantly reducing the BER value. At high Eb/No, the performance of PN + BCH is slightly better. This indicates that the effectiveness of signal coding and spreading is strongly influenced by channel conditions and noise levels. Code length, spreading type, and error correction method play an important role in optimizing digital communication performance.